The opinion of university students and teachers of education on degrowth: a mixed exploratory study - Trujillo Vargas, José Jesús; Díez Gutiérrez, E. J.; García Salas, L. M.; Aguilar Moya, S.; Romero Acosta, K. C.; Pérez Robles, A.; Perlado Lamo de Espinosa, I.; Mateos Toro, L. M. (My University, 2025)
Degrowth is proposed at a scientific and theoretical level as a possibility to curb climate change and thereby prevent a potential collapse. Educating about degrowth, therefore, emerges as an academic and social alternative for raising awareness among teachers and future generations. The objective of this mixed exploratory study is to understand the opinion of 419 university students and teachers with Education-related degrees (Bachelor’s and Master’s) regarding the climate crisis and degrowth education. A Likert-type questionnaire was used, which, as a pilot construct through the Delphi technique and the judgment of specialists and experts, enabled two analyses: one statistical-descriptive and the other content-based. In general terms, the results indicate that the participating students and teachers are partially aware of the need for a paradigm shift, recognizing that the future will involve experiencing a situation of planetary depletion and unsustainability. It is concluded that: a) the questionnaire surpasses its exploratory validation phase and maintains a correct relationship of relevance between items; and b) the educational opinion affirms that education on degrowth, as a cross-disciplinary content, is a key factor in counteracting collapse.
Keywords: climate change; degrowth; sustainability; teacher training; questionnaires